How will the world perceive livestock agriculture in relation to the impacts on, and of, climate change? - Thornton, Philip K. (International Livestock Research Institute, 2012)
The livestock sector globally consttutes a development conundrum: the benefts and the costs are both mult-faceted and highly context-specifc, and their honest appraisal defes simple analysis and easy categorizaton. In the past, changes in the demand for livestock products have been largely driven by human populaton growth, income growth and urbanizaton, and the producton response in diferent livestock systems has been associated with science and technology improvement as well as with increases in animal numbers. In the future, producton will increasingly be afected by competton for natural resources (partcularly land and water), competton between food and feed, and probably by the need to operate in a carbon-constrained economy. Demand in developed countries is likely to be afected by environmental and animal welfare legislaton and by human health concerns and changing socio- cultural values. On the other hand, in many developing countries, partcularly in Africa, livestock keeping will contnue to be a critcal asset to many millions of smallholders and pastoralists: many of these people have few if any other livelihood optons.